Aproveitamento do caroço de manga: um estudo de viabilidade da pirólise usando energia solar - Andrade, Laiane Alves de (2015)
Brazil has a fairly diversified energy matrix, whose main sources consist of the use of the hydroelectric potential of its rivers and oil reserves, the latter being a non-renewable energy and very polluting. Even if Whimsy percentage when compared to the usual forms of energy in Brazil (hydroelectric and oil), the country have meteorological and agro-industrial conditions suitable to be a great producer, potential, solar energy and chemical energy coming from biomass. With regard to biomass, Brazil is one of the biggest producers of this form of energy, especially in the form of waste. If the purpose is not the direct combustion, biomass can be converted into fuels or even the noblest same in chemical precursors to other sectors of the economy. That said this thesis was to investigate the pyrolysis characteristics of mango seed and then evaluate the viability of pyrolysis process using techniques of solar concentration. Was used as the residual biomass core sleeve due to the highlight of the fruit on the world stage and also regionally where about 1300 t/year are discarded this waste in the region. The sleeve core is divided into two main parts: the kernel and the husk, being rich in the first and second bioactive compounds mainly composed of lignin, cellulose and hemicellulose. With regard to the kernel, there was a significant range of bioactive compounds (phenolic, flavonoids, ascorbic acid and citric acid), with emphasis on phenolic compounds with a content of about 3000 mg/100 g and is high compared to other fruits studied as acerola seed, soursop and guava. Concerning the integument, this presented a good indicator for the formation of liquid products, high volatile content and low ash content. With respect to thermogravimetric analysis, it was evaluated in two stages: the first related to the loss of water (drying) and the second referring to the pyrolysis reactions . For the first stage, after studies nonlinear model best described the drying step was Henderson, yielding an average activation energy of about 20 kJ/mol. As for the second stage, isoconversionais models showed activation energy for 157-175 kJ/mol. The Independent Reactions model (RPI) showed activation energy between 70 and 78 kJ/mol, 160 and 190 kJ/mol and 90 and 97 kJ/mol for lignin, cellulose and hemicellulose, respectively. There was also a tendency of decrease in activation energy with decreasing particle size both in the drying step as described in the second step isocorversionais models (Ozawa and Kinssinger). For the RPI model this trend was observed only for the major component of biomass (cellulose). Analytical pyrolysis has shown that the temperature at 500°C was the most suitable for production of liquid. In the temperature to 350°C, had become a low energy cost and the production of furfural which is of commercial interest. Concerning the study of the feasibility of solar pyrolysis by Response Surface technique was possible to predict simulations the best combination of the size of the solar collector (D), the system size to be heated (d) and solar radiation (G ) for significant temperature levels for industrial applications requiring this condition (for example, pyrolysis). Numerical simulations showed good agreement with the experimental data of solar heating, showing that with the optimization of operating conditions, particularly the effective area of the paraboloid, it would be possible to reach temperatures capable of providing the pyrolytic conversions.